Association of dietary pattern with biochemical blood profiles and bodyweight among adults with Type 2 diabetes mellitus in Tehran, Iran - Zad, Nasrin Darani; Mohd Yusof, Rokiah; Esmaili, Haleh; Jamaluddin, Rosita; Mohseni, Fariba (BioMedical Central, 2015)
Background: This study was conducted to identify dietary patterns and evaluated their association with biochemical blood profiles and body weight among adults with type 2 diabetes mellitus.